2019
DOI: 10.1111/agec.12522
|View full text |Cite
|
Sign up to set email alerts
|

Participation in contract farming and farm performance: Insights from cashew farmers in Ghana

Abstract: The global demand for cashew nuts continues to increase steadily. However, many African countries face difficulties in marketing and adding value to the product. Using recent survey data of 391 cashew farmers in Ghana, this paper contributes to the growing evidence on the significance of contract farming (CF) in improving the welfare of rural households in developing countries. Specifically, the paper analyzes the factors that influence cashew farmers' decisions to participate in CF, and the impact of particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 39 publications
8
39
4
Order By: Relevance
“…However, performing this estimation using OLS assumes that CLDI is random and an exogenous variable, while it is non-random and potentially endogenous. The non-random sample selection problem originates from self-selection, in which farmers decide whether or not to engage in crop-livestock (2) [19,40,47] have suggested that the standard approach to deal with the problem of endogeneity and self-selection bias is the Instrumental Variable (IV) technique such as CMP framework.…”
Section: Conditional Mixed-processmentioning
confidence: 99%
“…However, performing this estimation using OLS assumes that CLDI is random and an exogenous variable, while it is non-random and potentially endogenous. The non-random sample selection problem originates from self-selection, in which farmers decide whether or not to engage in crop-livestock (2) [19,40,47] have suggested that the standard approach to deal with the problem of endogeneity and self-selection bias is the Instrumental Variable (IV) technique such as CMP framework.…”
Section: Conditional Mixed-processmentioning
confidence: 99%
“…In Table 3, the estimation result of the IV‐Oprobit model as larger than the model estimation result without the instrumental variable, which indicates that the instrumental variable mainly solved the missing variable problem. Because of this, the endogenous problem of reverse causality theoretically overestimated the role of explanatory variables 140,141 . At the same time, the direction and significance level of the estimated coefficient robustness test indicated that if the possibility of organizational participation increases, farmers were more likely to choose to participate in the joint control of pests and diseases with other farmers.…”
Section: Model Estimation and Resultsmentioning
confidence: 99%
“…Because of this, the endogenous problem of reverse causality theoretically overestimated the role of explanatory variables. 140,141 At the same time, the direction and significance level of the estimated coefficient robustness test indicated that if the possibility of organizational participation increases, farmers were more likely to choose to participate in the joint control of pests and diseases with other farmers. Thus, Hypothesis 4 was substantially verified.…”
Section: Model Estimation Of Hypothesis 4: Organizational Participatimentioning
confidence: 99%
“…Empirical model. It is very likely that since firms initiate the contract (Dubbert, 2019), a farmer's participation in contract farming depends largely on firm's criteria rather than farmer's choice. In this context, the binary logit model was used to identify the determinants of farmers' participation in contract farming.…”
Section: Methodsmentioning
confidence: 99%
“…In the model, participation or non-participation in contract farming was considered as a dependent variable, where a farmer who grew sunflower under contract was coded one (1), whereas a farmer who grew sunflower but not under contract was given a code zero (0). Several studies related to participation in this context (Opoku, 2012;Dubbert, 2019).…”
Section: Methodsmentioning
confidence: 99%